Contracting with long-term consequences - Suvi Vasama (Bank of Finland, 2017)
I examine optimal managerial compensation and turnover policy in a principal-agent model in which the firm output is serially correlated over time. The model captures a learning-by-doing feature: higher effort by the manager increases the quality of the match between the firm and the manager in the future. The optimal incentive scheme entails an inefficiently high turnover rate in the early stages of the employment relationship. The optimal turnover probability depends on the past performance and the likelihood of turnover decreases gradually with superior performance. Following weak performance, the contract implements a permanently inefficient turnover rate. With correlated outcome, a permanent inefficiency is needed to save on information rents to the agent, even when the agent does not have persistent private information.
URN:NBN:fi:bof-201708041451
Keywords: C73; D82; D86; 330